From global Doughnut sustainability to local tourism destination management - Lähteenmäki-Uutela, Anu; Haukioja, Teemu; Pohjola, Tuomas (Hotel and Tourism Management, 2024)
Purpose – This paper explores the intersection of global sustainability frameworks and local tourism management applying the Doughnut Economy model. The study aims to understand how destinations can bridge the gap between multidimensional, multilevel sustainability objectives and local execution, ultimately promoting a paradigm shift towards sustainable tourism. Methodology – We review the sustainable destination management literature as well as the Doughnut Economy framework and evaluate how the Doughnut model allows for an examination of how destinations can simultaneously address local needs and broader, systemic impacts. Findings – The integration of the Doughnut Economy model can help to ensure that the benefits and costs of tourism are in balance. Tourism destinations need to adopt consistent sustainable practices that align with both local aspirations and global sustainability targets. Digitalization can enhance the measuring and modelling of impacts and aid in steering behaviour. Implications – Destination managers have a role in the broader sustainability of tourism, and they will be required to apply comprehensive approaches such as the Doughnut model supported by digital solutions to balance social and ecological demands at local and global levels.